Failure of the Myth: The American West as Fraud - Jaupaj, Artur; Shumeli, Arjan (Mediterranean Journal of Social Sciences, 2012)
The American West has been mythologized for its uniqueness, endless economic opportunities and the decisive role it hasplayed in shaping the American character and democracy. As a matter of fact, Western mythology since its earliest times propagandizedthe West, despite its aridity and shortage of water, as â€œThe Garden of the Worldâ€ where the rugged and resourceful individual couldeasily secure a life full of abundance and live happily. Such Eden-like descriptions prevailed throughout the nineteenth century and wereeven renewed when the region was officially highlighted as the future of the nation and as a â€œsafety valveâ€ for economically poor citydwellers. However, 1930s would initiate a mounting opposition against the West and the publication of Walter Prescott Webbâ€™s TheGreat Plains (1930) would reshape, not only Turnerâ€™s regionalist and sectionalist ideas by portraying the Great Plains as a separatecultural entity, but also brand the Western topography with only one word, aridity. Eventually, the second half of the twentieth centuryproliferated in alternative fictional and historical representations of the West and marked the rise of a new type of Western whichparodied and reversed the formula conventions for different ends. Likewise, E. L. Doctorow`s Welcome to Hard Times (1960), shattersthe happy ending of the classic Western by re-presenting the cyclical failure of a frontier town. In addition, neither the hero, portrayed asa short-sighted coward nor the other characters, depicted as materialistic and self-centered, nor the topography, described asuninhabitable, fulfill the requirements of the genre. Furthermore, Welcome to Hard Times, depicts the western mythology of progress andabundance as fraudulent as it is based on â€œget in, get rich, get outâ€ (Limerick, 1987: 100) economic schemes.